Inter-individual responses of post-exercise hypotension in older adults with hypertension: An exploratory analysis of different exercise modalities - Carpes, Leandro O.; Domingues, Lucas B.; Bertoletti, Otávio; Fuchs, Sandra C.; Ferrari, Rodrigo (Frontiers in Physiology, 2022)
Background: Various physical exercise modalities can acutely reduce blood pressure (BP). However, not all individuals respond similarly after an exercise session. Purpose: To measure inter-individual variations in 24-h BP after a single bout of various exercise modalities in older adults with hypertension. Methods: This retrospective study analyzed data from participants with hypertension (≥ 60 years) previously included in three randomized controlled trials on this topic. BP was assessed using ambulatory BP monitoring. We compared the mean changes in total 24-h, daytime, and nighttime BP after aerobic (AE, n = 19), combined (COMB, n = 19), resistance (RES, n = 23), and isometric handgrip (ISO, n = 18) exercise sessions to a non-exercising control session (C). The minimum detectable changes to classify the participant as a “Responder” for the corresponding exercise protocol were 4 and 2 mmHg for systolic and diastolic BP, respectively. Results: The prevalence of Responders for systolic BP was as follows: AE 24-h: 37%, daytime: 47% and nighttime: 37%; COMB 24-h: 26%, daytime: 21% and nighttime: 32%; RES 24-h: 26%, daytime: 26% and nighttime: 35%; and ISO 24-h: 22%, daytime: 22% and nighttime: 39%. For diastolic BP, the prevalence of Responders was as follows: AE 24-h: 53%, daytime: 53% and nighttime: 31%; COMB 24-h: 26%, daytime: 26% and nighttime: 31%; RES 24-h: 35%, daytime: 22% and nighttime: 52%; and ISO 24-h: 44%, daytime: 33% and nighttime: 33%. Conclusion: There was a high inter-individual variation of BP after a single bout of various exercises in older adults. Responders had higher BP values on the control day without exercise. Various exercise modalities might acutely reduce 24-h BP in older adults with hypertension.